COMPARISON OF ANTIOXIDANT AND ANTI-TYROSINASE ACTIVITY BETWEEN BLACK SOYBEAN (GLYCINE MAX (L.) MERR.) AND DAIDZEIN - Delken Kuswanto; I Nyoman Ehrich Lister; Ermi Girsang; Ali Napiah Nasution; Wahyu Widowati (Buletin Farmatera, 2020)
Free radicals in the body will increase with excessive of ultraviolet (UV) light exposure, induce oxidative stress with the formation of Reactive Oxygen Species (ROS). A visible effect on skin tissue known as photoaging, including the process of melanogenesis catalyzed by the tyrosinase enzyme, risked for pigmentation or melanoma disorder.The use of natural ingredients has been widely used by the community to prevent the aging process. Natural compounds from a plant can be a source of antioxidants and have anti-aging abilities through inhibition of the tyrosinase enzyme. Black soybean (Glycine max (L.) Merr.) are high in isoflavone compound, one of which is daidzein.This study evaluates the antioxidant and anti-aging potential of black soybean extract with daidzein. Antioxidants using the DPPH method and anti-aging tests carried out, namely the inhibition of the tyrosinase enzyme, are very important in the aging process.Daidzein has an IC50 value of DPPH scavenging activity around 109.34±2.80 µg/mL lower than black soybean extract with 116.52±2.50 µg/mL. Results on tyrosinase enzyme inhibition activity, black soybean extract had an IC50 value of 70.71±1.83 µg/mL lower compared to daidzein with 72.65±2.81 µg/mL. In contrast to the better antioxidant activity of daidzein, the black soybean extract are more potential to inhibit the enzyme tyrosinase